IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN MATEMATIKA PESERTA DIDIK KELAS III SD N LEDOK 2 SALATIGA - Dinda Adelia Litasari; Martha Nandari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The learning model used by the teacher still uses the lecture method so that students do not understand the material that has been presented. Thus, it is necessary to apply a learning model that suits these problems. Problem based learning (PBL) is a problem-based learning model. The problems faced are problems that are in accordance with students' real lives. The Problem Based Learning model emphasizes problem solving activities in learning. The application of the Problem Based Learning model is an appropriate alternative for involving all students to play an active role in learning and developing thinking skills, because all learning in it is linked to everyday problems. This research uses a descriptive qualitative approach that describes improving student learning outcomes with this type of classroom action research. Data was taken using the observation method. The results of this study show that there is an increase in learning outcomes in class III mathematics subjects